Stress among medical students: A short communication on prevalence, sources, and implications - Ruffeel, Raashidhah; Pathberiya, Michelle Disansa; Rajantheran, Laavanya A/P K.; Cheong, Vivian; Nursham, Ahmad Firdaus Bin Azlan (Journal of Biomedical Sciences, 2025)
Background: Stress among medical students is a global concern with implications for academic performance, psychological well-being, and future professional competence. Research indicates a consistently high prevalence of stress across diverse educational settings, while coping strategies adopted by students vary considerably, thereby influencing outcomes. This short communication integrates current evidence regarding prevalence, determinants, and—most importantly—coping strategies adopted by medical students. Enhancing adaptive coping strategies and bolstering the institutional support framework could mitigate negative outcomes and cultivate resilience in medical training.